Chemodivergent hydrogenolysis of eucalyptus lignin with Ni@ZIF-8 catalyst. Issue 6 (26th February 2019) - Liu, Xue; Li, Helong; Xiao, Ling-Ping; Sun, Run-Cang; Song, Guoyong
Abstract : Chemodivergent hydrogenolysis of eucalyptus biomass leading to 4-propanol- or 4-propyl-substituted phenols, together with a well-preserved carbohydrate component, was achieved by using Ni@ZIF-8 catalyst. Abstract : Reductive catalytic fractionation (RCF) of lignocellulosic biomass, that is depolymerization of the native lignin component into well-defined monomeric phenols in the first step, offers an opportunity to utilize entire biomass components. Herein, we report that Ni@ZIF-8 can serve as a chemodivergent catalyst in RCF of eucalyptus sawdust, thus selectively producing phenolic compounds having either a propyl or propanol end-chain under different reaction conditions. In both cases, high yields of lignin monomers and a high degree of delignification were achieved, next to well-preserved carbohydrate pulp suitable for further processing. A mechanistic study using model compounds indicated that the dehydroxylation at the γ-position of the β- O -4 structure may be involved in the selectivity-controlling step.